2020
DOI: 10.1021/acs.jpcc.9b11423
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Chemically Modified Graphene Sheets to Enhance Etching of Ge Surface in Water

Abstract: We examined chemical etching of the Ge surface assisted by single sheets of chemically modified graphene in O2-containing water. Three types of graphene sheets were used: graphene oxide (GO), hydrazine-reduced GO (hyd-rGO), and hydrothermally treated GO in an ammonia solution (amm-rGO). amm-rGO possessing pyridinic-N atoms produced the highest etching rates of the graphene used for all water temperatures tested. We propose that graphene sheets catalyze Ge oxidation underneath the sheets and that this phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Activation energy of Ge MacEtch along (100) direction was calculated using Arrhenius equation as follows: 30,36…”
Section: Effect Of Kmno4 Concentration and Temperature On Ge Macetchmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation energy of Ge MacEtch along (100) direction was calculated using Arrhenius equation as follows: 30,36…”
Section: Effect Of Kmno4 Concentration and Temperature On Ge Macetchmentioning
confidence: 99%
“…For example, Kim et al 29 However, it should be mentioned that hydrofluoric (HF) acid, an extremely toxic and highly corrosive acid, should be avoided as much as possible. It has been reported that DI water can be only used as etching solution, 27,30 but they suffered from low etch rate (20 ~ 30 nm/h at high temperature) and difficult control of the amount of O2 dissolved in DI water. In addition, their antireflection property was only analyzed from visible to NIR range up to cut-off wavelength of Ge (1550 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, carbon materials have been focused on as alternative catalysts for these etching reactions. The motivation of utilizing carbon materials in assist-etching is to catalyze the oxygen or H 2 O 2 reduction reactions. These materials have inherent edges and defects, which alter the local density of the π-electrons, and such areas can serve as active sites for oxidant reduction reactions . In previous reports, graphene, carbon nanotube, and carbon nanospheres have been used to catalyze silicon etching reactions in an HF–H 2 O 2 solution or vapor. …”
Section: Introductionmentioning
confidence: 99%
“…To conduct the abovementioned new etching mode, catalytic materials ranging from noble metals to nanocarbons , must be deposited on a semiconductor surface before chemical etching enhances its dissolution. This is achieved using various methods, such as electroless deposition, evaporation, and spin coating . For example, Peng et al demonstrated electroless Ag deposition on Si, followed by Ag-nanoparticle-catalyzed chemical etching of Si in an HF/Fe­(NO 3 ) 3 solution to form large-area, highly oriented one-dimensional Si nanostructure arrays .…”
Section: Introductionmentioning
confidence: 99%